Recent advances in mechanism design for robotics : proceedings of the 3rd IFToMM Symposium on Mechanism Design for Robotics /: proceedings of the 3rd IFToMM Symposium on Mechanism Design for Robotics. ([2015]) - Unknown
No abstract available